Old-Fashioned Ethics and Common-Sense Metaphysics : With Some of Their Applications - Thornton, William Thomas, 1813-1880 (Salt Lake City, UT : Project Gutenberg, 2009)
"Old-Fashioned Ethics and Common-Sense Metaphysics" by William Thomas Thornton is a philosophical treatise written in the late 19th century. The work delves into ethical principles and metaphysical inquiries, focusing particularly on common-sense approaches to understanding morality, duty, and the human condition. Thornton critiques utilitarianism, exploring the implications of pleasure as the primary object of ethical consideration, while emphasizing the importance of virtue and duty as central to a moral framework. The opening of this thought-provoking work sets the stage for a critical examination of utilitarianism, presenting it as a doctrine that reduces morality to the pursuit of pleasure while failing to account for deeper ethical obligations. Thornton begins by laying out the tenets of utilitarianism and then proceeds to challenge its core tenets through a series of moral dilemmas and thought experiments, arguing that true virtue often requires self-denial and prioritizing the welfare of others over one's own enjoyment. He posits that morality transcends mere utility and calls for a return to ethical principles rooted in duty and virtue, suggesting that a rich moral life cannot be reduced to the pursuit of individual happiness. (This is an automatically generated summary.)
Release date is 2009-09-06
E-text prepared by Barbara Tozier, Bill Tozier, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Utilitarianism; Metaphysics